The Kantian view of dark representations and their function in practical life, according to the anthropological notes of the Critical Period - Martínez, Luciana (Studia Kantiana, 2023)
This contribution examines the doctrine of dark representations as it is presented in the anthropological annotations of the critical period. The explanation of such representations is analysed, taking into account the analogies used for this purpose. Three kinds of manifestations of such representations in everyday life are then considered: our connection with death and fear, the development of certain feelings, such as respect, and their effects, and the way we produce philosophical knowledge.